2008
DOI: 10.2337/dc08-0914
|View full text |Cite
|
Sign up to set email alerts
|

Multitissue Insulin Resistance Despite Near-Normoglycemic Remission in Africans With Ketosis-Prone Diabetes

Abstract: African patients with KPD with an average 10.5-month insulin-free near-normoglycemic remission period (mean A1C 6.2%) were compared with 17 control subjects matched for age, sex, BMI, and geographical origin. Insulin stimulation of glucose disposal, and insulin suppression of endogenous glucose production (EGP) and nonesterified fatty acids (NEFAs), was studied using a 200-min two-step (10 mU ⅐ m Ϫ2 body surface ⅐ min Ϫ1 and 80 mU ⅐ m Ϫ2 ⅐ min Ϫ1 insulin infusion rates) euglycemic clamp with [6,6-2 H 2 ]glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…The period of near-normoglycemia remission is variable, with some studies reporting remission lasting between 6 and 120 months (10,13). Despite the initial improvement, most obese African American patients with DKA and severe hyperglycemia (12,16) have a gradual decline in their β-cell function (10) with continued insulin resistance (15) if treated with diet alone. Previous studies with sulfonylureas showed prolongation of near-normoglycemia remission in obese African American patients with an initial presentation of DKA and severe hyperglycemia (12,16), but sulfonylurea treatment may increase the risk for hypoglycemia and weight gain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The period of near-normoglycemia remission is variable, with some studies reporting remission lasting between 6 and 120 months (10,13). Despite the initial improvement, most obese African American patients with DKA and severe hyperglycemia (12,16) have a gradual decline in their β-cell function (10) with continued insulin resistance (15) if treated with diet alone. Previous studies with sulfonylureas showed prolongation of near-normoglycemia remission in obese African American patients with an initial presentation of DKA and severe hyperglycemia (12,16), but sulfonylurea treatment may increase the risk for hypoglycemia and weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Despite significant improvement in insulin secretion and insulin action at the time of remission from insulin (1,14,15), many patients experience recurrence of hyperglycemia if treated with diet alone (10). Few studies have focused on the optimal treatment to prolong the period of near-normoglycemia remission in obese African American patients with DKA and severe hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%
“…11 As with type 1 diabetes, exogenous insulin is needed to treat the ketoacidosis. However, once the acute metabolic derangement of hyperglycaemia and accelerated lipolysis (the cause of the ketosis) is reversed with insulin, both β cell function and insulin sensitivity improve.…”
Section: How Does Ketosis Prone Type 2 Diabetes Differ From Hyperosmomentioning
confidence: 99%
“…At the onset, KPD often appears as type 1 diabetes with acute hyperglycemia and ketosis or ketoacidosis and the obvious need for insulin therapy but the signs of autoimmunity against islet β-cells are absent. In contrast, during near-normoglycemic remission, patients with KPD usually display multisite insulin resistance similar to that seen in type 2 diabetes (4,5). In 2008, Sobngwi et al (6) hypothesized that KPD is a subtype of type 2 diabetes with acute onset at diagnosis as the result of an environmental factor such as a human herpes virus infection that would severely impair glucose-stimulated insulin secretion and favor ketogenesis.…”
Section: Classification Of Diabetesmentioning
confidence: 99%